Thyroid Abscess Initially Presenting as Destructive Thyroiditis With Subsequent Hypothyroidism - Caseja, Ahl Jeffrey (J Endocr Soc, 2021)
Introduction: Due to its rich vascular supply and high iodine content infection of the thyroid gland is rare and is uncommonly associated with hyperthyroidism. We report a case of a thyroid abscess presenting with hyperthyroidism with subsequent hypothyroidism in an immunocompetent patient. Clinical Case: A 34-year old female with no past medical history presented with an enlarging neck mass associated with worsening, non-radiating throat pain of three-week duration associated with dysphagia. She reports 15-lb weight loss and palpitations. On presentation vital signs were within normal range. Physical examination revealed a diffusely tender anterior neck mass. Her thyroid function tests revealed TSH 0.01 uIU/mL (0.358-3.74), FT4 2.4 ng/dL (0.76-1.46), TSI <0.10 IU/L (0.00-0.55), TPO 12 IU/mL (0-34). Laboratory workup was also significant for leukocytosis, thrombocytosis, and hyponatremia. Thyroid ultrasound revealed a large, irregularly shaped, multiloculated fluid collection involving both lobes measuring 6.4 x 4.8 x 2.0 cm. She was started on Vancomycin and Ampicillin/Sulbactam, Metoprolol, and Methimazole. Needle aspiration of 30 cc of purulent material was performed with culture showing a heavy growth of streptococcus constellatus sensitive to penicillin. After a 4-day inpatient stay, she was discharged with Amoxicillin/Clauvanate as well as Methimazole 10mg BID. Ten days after being discharged, the patient again presented to the emergency department with complaint that the neck mass had increased in size. CT neck showed a 5.1 x 2.8 x 0.8 cm lobulated fluid collection. CT-guided drainage was performed, cytology and wound culture were found to be unremarkable. Thyroid function tests revealed she was hypothyroid with TSH 31.157 uIU/mL and FT4 of 0.72 ng/dL. Upon discharge, Methimazole was discontinued and she was started on Levothyroxine 75 mcg daily. Due to failure of prior antibiotics, she received a 14-day course of IV Ceftriaxone. Outpatient follow-up eight weeks later showed she was euthyroid on Levothyroxine 75 mcg with ultrasound revealing small thyroid gland with resolution of the abscess. Conclusion: Hyperthyroidism in the setting thyroid abscess is secondary to destructive thyroiditis. As there is no increase in thyroid hormone synthesis, there is no role for treatment with antithyroid medication. Symptomatic control with beta-blocker, surgical drainage, and IV antibiotics are recommended for cases of thyroid abscesses. If infection persists or extensive necrosis develops, thyroidectomy may be indicated. Hypothyroidism can be a consequence of destructive thyroiditis as was seen in this patient.